2008
DOI: 10.1083/jcb.200802091
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II has distinct functions in PNS and CNS myelin sheath formation

Abstract: The myelin sheath forms by the spiral wrapping of a glial membrane around the axon. The mechanisms responsible for this process are unknown but are likely to involve coordinated changes in the glial cell cytoskeleton. We have found that inhibition of myosin II, a key regulator of actin cytoskeleton dynamics, has remarkably opposite effects on myelin formation by Schwann cells (SC) and oligodendrocytes (OL). Myosin II is necessary for initial interactions between SC and axons, and its inhibition or down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
138
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(153 citation statements)
references
References 54 publications
(94 reference statements)
15
138
0
Order By: Relevance
“…8F). Of note, pronounced ensheathment defects were also observed in SCs lacking MLC (Wang et al, 2008), thus confirming that myosin II activity is required for proper axonal segregation. Thus, despite undergoing differentiation, shMLCKtreated SCs are unable to properly segregate axons and therefore unable to myelinate.…”
Section: Knockdown Of Mlck Impairs Radial Sorting Of Axons By Schwannmentioning
confidence: 61%
See 2 more Smart Citations
“…8F). Of note, pronounced ensheathment defects were also observed in SCs lacking MLC (Wang et al, 2008), thus confirming that myosin II activity is required for proper axonal segregation. Thus, despite undergoing differentiation, shMLCKtreated SCs are unable to properly segregate axons and therefore unable to myelinate.…”
Section: Knockdown Of Mlck Impairs Radial Sorting Of Axons By Schwannmentioning
confidence: 61%
“…Of interest, a similar correlation between downregulation of acto-myosin contractility and membrane extension has been recently described during morphological differentiation of oligodendrocytes (Kippert et al, 2009), suggesting that despite their different morphologies and modes of myelination, the mechanisms controlling plasma membrane expansion by myelinating glial cells require local release of myosin-II-mediated contraction and relaxation of the actin cytoskeleton. Whether MLCK activity also plays a role in oligodendrocyte remodeling and differentiation awaits further study, but inactivation of RhoA and ROCK as well as inhibition of myosin II have been shown to promote membrane expansion and oligodendrocyte branching and differentiation (Kippert et al, 2007;Wang et al, 2008;Wolf et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56) Myosin II is a hexameric complex composed of 2 myosin heavy chains, 2 MLCs, and 2 essential light chains. 57) Levels of non-muscle myosin II decrease as a function of oligodendrocyte differentiation and inhibition of myosin activity increases branching and myelination, 58,59) although their expression levels correlate negatively with myelination. 59,60) The demyelination observed in neuropathic pain due to nerve lysophosphatidic acid-induced injury occurs on Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…57) Levels of non-muscle myosin II decrease as a function of oligodendrocyte differentiation and inhibition of myosin activity increases branching and myelination, 58,59) although their expression levels correlate negatively with myelination. 59,60) The demyelination observed in neuropathic pain due to nerve lysophosphatidic acid-induced injury occurs on Schwann cells. 61) By immunofluorescence staining, we observed that MLC2 was increased by global cerebral ischemia in the sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%